Partnership policing and the dynamics of administrative growth - Stenström, Anders (Policing and society, 2023)
The current article reports findings from a research project on partnership policing in Stockholm, Sweden, to investigate how partnership policing strategies translate into social action. Consideration is given to the ways in which police officers and city employees produce chains of administrative tasks as they navigate their institutional environment and strive to produce legitimacy for partnership policing. More broadly, the findings suggest that the inner mechanisms of a partnership approach to policing are shaped by the self-referential (Eigendynamik) character of administration. The article discusses implications for partnership policing and for the broader literature on policing.